Comparison of lipopolysaccharides from Agmenellum quadruplicatum to Escherichia coli and Salmonella typhimurium by using thin-layer chromatography. - Buttke, T M (1975)
Lipopolysaccharide (LPS) was isolated from the unicellular blue-green bacterium Agmenellum quadruplicatum using the procedure of Westphal and Jann (1965). It was composed of a lipid A and polysaccharide region suggesting a similarity to other gram-negative LPSs. Chemical analyses demonstrated the presence of glucose, rhamnose, mannose, and xylose in the polysaccharide region, as well as 2-keto-3-deoxyoctonate, glucosamine, and phosphorous in the lipid A. Studies on the lipid composition revealed the presence of palmitic, behenic, and three beta-hydroxy fatty acids. A new procedure for thin-layer chromatography of bacterial LPSs was used to compare LPS from A. quadruplicatum to other gram-negative organisms. The method is capable of distinguishing between LPSs of different bacteria as well as between the wild-type organism and mutated forms unable to synthesize complete LPS. A comparison of LPS from A. quadruplicatum to Escherichia coli and Salmonella typhimurium demonstrated that, although the blue-green LPS was rather similar to that of the Enterobacteriaceae, distinct differences also existed. However, when several cell division mutants of A. quadruplicatum were compared chromatographically to the parent strain BG-1, no differences were observed. This suggests that cell division mutations in A. quadruplicatum are not associated with changes in the LPS.